2011
DOI: 10.1007/s00425-011-1547-0
|View full text |Cite
|
Sign up to set email alerts
|

The chloroplast ribosomal protein L21 gene is essential for plastid development and embryogenesis in Arabidopsis

Abstract: Embryogenesis in higher plants is controlled by a complex gene network. Identification and characterization of genes essential for embryogenesis will provide insights into the early events in embryo development. In this study, a novel mutant with aborted seed development (asd) was identified in Arabidopsis. The asd mutant produced about 25% of albino seeds at the early stage of silique development. The segregation of normal and albino seeds was inherited as a single recessive embryo-lethal trait. The gene disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 62 publications
6
44
2
Order By: Relevance
“…3E). Growth arrest at the globular stage of embryo development has been reported for several other mutants deficient in plastid ribosomal proteins (like prps20, prpl1, prpl4, prpl21, prpl27, or prpl35; Romani et al, 2012;Yin et al, 2012). Taken together, these analyses suggest that the loss of RH50, like that of GUN1, generally tends to potentiate the effects of mutations in genes for plastid ribosomal subunits (such as prors1, prps1, prps21, prpl11, and prpl24).…”
Section: Rh50 and Gun1: Coexpression And Colocalizationsupporting
confidence: 48%
“…3E). Growth arrest at the globular stage of embryo development has been reported for several other mutants deficient in plastid ribosomal proteins (like prps20, prpl1, prpl4, prpl21, prpl27, or prpl35; Romani et al, 2012;Yin et al, 2012). Taken together, these analyses suggest that the loss of RH50, like that of GUN1, generally tends to potentiate the effects of mutations in genes for plastid ribosomal subunits (such as prors1, prps1, prps21, prpl11, and prpl24).…”
Section: Rh50 and Gun1: Coexpression And Colocalizationsupporting
confidence: 48%
“…Furthermore, genes involved in calcium and calmodulin signaling network were the core components of C2, C3, most of which are represented by CDPK gene families (IRE4, bam1, ERECTA, HSL1, At1g74360, and IKU2) and MAPK cascade (MKK9) (Supplementary Table S6 in Supplementary Material). Genes involved in chloroplast development play a critical role in adapting stress environments (Yin et al, 2012). Interestingly, the C4 cluster contained multiple marker genes associated with protein synthesis by maintaining the chloroplast membrane system, including chloroplast ribosome proteins (RPL3, RPL5, RPL23, RPL28C, and RPL4A), thylakoidal processing peptidase 1 (TPP1), elongation factor TU GTP-binding domain (Eftud1).…”
Section: Resultsmentioning
confidence: 99%
“…The function of the nucleus-encoded plastid ribosomal proteins has been studied mainly in the model plant Arabidopsis by using publicly available T-DNA insertion lines (Pesaresi et al, 2001; Morita-Yamamuro et al, 2004; Bryant et al, 2011; Tiller et al, 2012; Romani et al, 2012), mutants generated by RNAi approaches (Tiller et al, 2012), or mutants identified in EMS mutagenesis screens (Yin et al, 2012). Due to the lack of a chloroplast transformation system for Arabidopsis , the essentiality of plastid-encoded ribosomal proteins has been exclusively investigated in tobacco ( Nicotiana tabacum ).…”
Section: Essential and Non-essential Components Of The Plastid Translmentioning
confidence: 99%